Metabolic and Toxic Myelopathies - Slama, Michaël C. C.; Berkowitz, Aaron L. (Seminars in Neurology, 2021)
Metabolic and toxic causes of myelopathy form a heterogeneous group of disorders. In this review, we discuss the causes of metabolic and toxic myelopathies with respect to clinical presentation, pathophysiology, diagnostic testing, treatment, and prognosis. This review is organized by temporal course (hyperacute, acute, subacute, and chronic) and etiology (e.g., nutritional deficiency, toxic exposure). Broadly, the myelopathies associated with dietary toxins (neurolathyrism, konzo) and decompression sickness present suddenly (hyperacute). The myelopathies associated with heroin use and electrical injury present over hours to days (acutely). Most nutritional deficiencies (cobalamin, folate, copper) and toxic substances (nitrous oxide, zinc, organophosphates, clioquinol) cause a myelopathy of subacute onset. Vitamin E deficiency and hepatic myelopathy cause a chronic myelopathy. Radiation- and intrathecal chemotherapy-induced myelopathy can cause a transient and/or a progressive syndrome. For many metabolic and toxic causes of myelopathy, clinical deficits may stabilize or improve with rapid identification and treatment. Familiarity with these disorders is therefore essential.
Keywords: metabolic; toxic; myelopathy; myeloneuropathy